THE DESIGN, MODELING AND EVALUATION OF POTENTIAL HIV PROTEASE INHIBITORS USING BLITZ, AN INTERACTIVE COMPUTER GRAPHICS WORKING TOOL (Journal of Sciences, Islamic Republic of Iran)
Several nonpeptide small molecules were designed as potential inhibitors of HIV protease and their structures were constructed by computer-aided molecular modeling and docked iwo the active site of HIV protease. Models of the complexes of inhibitors and the HIV protease were refined using nonbonded and H-bonding terms. The refined energy of selected complexes showed that the designed inhibitors fitted tightly into the active site of receptor cavity. The structure of the designed inhibitor (HI-082) was superimposed on the molecule of haloperidol (which has been reported to have anti-HIV protease activity) and it was found that they share a number of common structural features. These results showed that these small nonpeptide molecules interact strongly with the HIV protease and may therefore inhibit its action in which case they would be potential anti-AIDS agents